(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
This paper aims to defend the use of both qualitative and quantitative methods in research in language philosophy. Specifically, I would argue that the best option for conducting this type of research is to use methods of corpus linguistics, but also applying qualitative methods. For this, I will argue in favor of the idea of virtuous loops, feedback processes between both methods that can produce findings that would be impossible to discover if only one of the two methods were used.